Beyond Pairwise Interactions: How Other Species Regulate Competition Between Two Plants? - Wang-Xin Cheng; Wei Xue; Jie-Jie Jiao; Hao-Ming Yuan; Lin-Xuan He; Xiao-Mei Zhang; Tao Xu; Fei-Hai Yu (Plants)
A plant species in a community often grows with some other plant species. While many studies have assessed interspecific interactions between two target plant species, few have considered the impacts of the other plant species (e.g., the third, fourth, and fifth plant species) on these interactions. To assess the impacts, we grew one seedling of each of the five herbaceous plant species that are common in China (Cynodon dactylon, Plantago asiatica, Taraxacum mongolicum, Nepeta cataria, and Leonurus japonicus) alone (no competition) or with one seedling of one, two, three, or four of the other species. The presence of a neighbor plant generally reduced the growth of the target species, suggesting that the interspecific relationships were mostly competitive. The presence of other neighbor species (the third, fourth, and fifth species) could alter the interspecific interactions between two target species, but such effects varied depending on both the identity of the target species and the identity of the other species. Additionally, the effects of the third species depended little on the presence of the fourth and fifth species. We conclude that interspecific interactions between two plant species are commonly regulated by the presence of other species, facilitating species coexistence. However, our findings do not support the idea that the impacts of the fourth and fifth species on interactions among three plant species are common. This study highlights the complex interactions among multiple plant species within a community and also the importance of including these high-order interactions when modelling community dynamics and species coexistence.